Meretas Pemikiran Ekumenisme Eka Darmaputera:: Sentilan dan Persuasi bagi Gereja-gereja di Indonesia - Gerald Moratua Siregar (Institut Agama Kristen negeri Kupang, 2022)
In Indonesia, concern for the unity of the Church in Indonesia began in the early twentieth century. The ecumenical movement in Indonesia at that time was still being started sporadically by several church associations. Then on May 25, 1950, on the idea of ??several church synods, Dewan Gereja Indonesia (the Indonesian Council of Churches-ICC) was established, which later changed its name to Persekutuan Gereja-gereja di Indonesia (the Communion of Churches in Indonesia-CCI). Today, Persekutuan Gereja-gereja di Indonesia has increased to 95 church synods. On the one hand, the Church needs to be proud, because it seems that concern for the unity of the Church is getting higher. But on the other hand, a critical question arises whether through PGI the Church is truly united? What is really an indicator of the unity of the Church? Because in some cases and contexts, there is still separation and alienation among churches in Indonesia. Through this article, the author invites the reader to carefully look at the essence of Eka Darmaputera's thoughts on the unity of the church, which of course can be used as an important recommendation for the realization of the complete unity of the church.